2014
DOI: 10.1042/an20130034
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Patterns of Cortical Proliferation of Glial Cell Populations after Traumatic Brain Injury in Mice

Abstract: TBI (traumatic brain injury) triggers an inflammatory cascade, gliosis and cell proliferation following cell death in the pericontusional area and surrounding the site of injury. In order to better understand the proliferative response following CCI (controlled cortical impact) injury, we systematically analyzed the phenotype of dividing cells at several time points post-lesion. C57BL/6 mice were subjected to mild to moderate CCI over the left sensory motor cortex. At different time points following injury, mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
78
2
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(93 citation statements)
references
References 58 publications
11
78
2
2
Order By: Relevance
“…In our study, GFAP was used as a specific marker of reactive astrocytosis (Eng et al, 2000), and a statistically significant increase in its expression was shown in the injured rat cortex following LFPI. This is in agreement with previously published findings obtained in the same (Di Giovanni et al, 2005;Okimura et al, 1996), and also in the other TBI models (Liu et al, 2014;Nonaka et al, 1999;Susarla et al, 2014). Results of the present study also revealed that pioglitazone used in our experimental conditions did not significantly change the level of reactive astrocytosis in the injured animals.…”
Section: Parameters Of Inflammationsupporting
confidence: 95%
“…In our study, GFAP was used as a specific marker of reactive astrocytosis (Eng et al, 2000), and a statistically significant increase in its expression was shown in the injured rat cortex following LFPI. This is in agreement with previously published findings obtained in the same (Di Giovanni et al, 2005;Okimura et al, 1996), and also in the other TBI models (Liu et al, 2014;Nonaka et al, 1999;Susarla et al, 2014). Results of the present study also revealed that pioglitazone used in our experimental conditions did not significantly change the level of reactive astrocytosis in the injured animals.…”
Section: Parameters Of Inflammationsupporting
confidence: 95%
“…This process begins with an expansion of the NG2+ cell population that is contributory to the forming glial scar. A predominantly microglial cell proliferation then appears to follow (Susarla et al, 2014). This sequence of cell proliferation and cell invasion to form the glial scar is also termed reactive gliosis.…”
Section: Accepted Manuscriptmentioning
confidence: 95%
“…This observation may help explaining the low number of cells with immature neuron phenotype reported in the peri-injury zone, both in our and in other models of traumatic brain injury (Susarla et al 2014).…”
Section: Discussionmentioning
confidence: 69%
“…However, nestin re-expression can also take place in situ (in resident cells) in the adult brain damaged region during formation of the glial scar (Michalczyk and Ziman 2005). Notably, the emergence of a small number of DCX-positive cells in the neocortex after its injury was reported in a mouse model (Susarla et al 2014). Yet another source of these cells may be NG2-positive mesenchymal stem cells that have neural lineage potential (Okolicsanyi et al 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation